A novel samarium(ii) complex bearing a dianionic bis(phenolate) cyclam ligand: synthesis, structure and electron-transfer reactions. Issue 9 (28th January 2016) - Maria, Leonor; Soares, Marina; Santos, Isabel C.; Sousa, Vânia R.; Mora, Elsa; Marçalo, Joaquim; Luzyanin, Konstantin V.
Abstract : A novel divalent samarium complex anchored on a dianionic bis(phenolate) ligand is reported and reactivity studies demonstrate that it is highly effective in inducing single-electron transfer processes. Abstract : The reaction of the hexadentate dianionic 1, 4, 8, 11-tetraazacyclotetradecane-based bis(phenolate) ligand, ( t Bu2 ArO)2 Me2 -cyclam 2−, with [SmI2 (thf)2 ] in thf resulted in the formation of the divalent samarium complex [Sm(κ 6 -{( t Bu2 ArO)2 Me2 -cyclam})] (1 ). X-ray diffraction studies revealed that after recrystallization from n -hexane/thf complex1 has a monomeric structure and does not contain thf molecules coordinated to the Sm(ii ) center. However, UV-vis and 1 H NMR spectroscopy of1 evidenced the formation of thf-solvated complexes in neat thf. Reductive studies show that complex1 can act as a single electron-transfer reagent and form well-defined Sm(iii ) species. The reaction of1 with several substrates, namely, TlBPh4, pyridine N -oxide, OPPh3, SPPh3 and bipyridines, are reported. Spectroscopy studies, including NMR, and single crystal X-ray diffraction data are in agreement with the formation of cationic Sm(iii ) species, monochalcogenide bridged Sm(iii ) complexes and Sm(iii ) complexes with bipyridine radical ligand, respectively.